(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Choosing the best course and considering one’s future career can be challenging for incoming college students. Some students know which course to take, while others still determine which will lead them there. In fact, because of the enormous number of courses available to students, most of them change majors. Selecting a degree and accessible courses is critical for every student because it is the foundation for future success. Students must be informed about their path to prepare for their future careers. They enter with certain goals, including finishing college and staying at their current institution. They enter a social system where peer group interactions and faculty interactions foster social integration, and they enter an academic system characterized by grade performance and intellectual development that foster academic integration. This study utilized the descriptive research design, which the researcher applied to gather the necessary data about student retention factors in the Hospitality Management Program at Bestlink College of the Philippines for A.Y. 2021-2022. The researcher gathered data using survey questionnaires administered via Google Forms to fifty (50) target respondents at Bestlink College of the Philippines. The survey revealed that most respondents were 22 years old, ranked one at 54%, followed by 21, ranked two at 28%, mostly female from BSHM students. Based on the results, more than half of the respondents were female, 72%, while the minority were male, with 28%. The results show that hospitality and services is a course preferred by women. Based on the gathered data and conclusions, the researchers formulated guidelines to improve student retention in Hospitality Management at Bestlink College of the Philippines. These guidelines include that most students can catch up or learn more due to the many ways they can learn from the subject. Most teachers are more creative in teaching the subject in ways that students can easily learn. They motivate their students to pursue and reach their dreams, for them never to give up and surpass all the challenges they encounter. This will give a good relationship to each other.